2018
DOI: 10.1038/s41598-018-27251-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating jealous behaviour in dogs

Abstract: The function of jealous behaviour is to facilitate the maintenance of an important social relationship that is threatened by a third-party, a rival individual. Although jealous behaviour has an important function in gregarious species, it has been investigated almost exclusively in humans. Based on functional similarity between dog-owner and mother-infant attachments, we hypothesised that jealous behaviour can be evoked in dogs, similarly to children. In our study owners focused their attention solely on the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Thus, to the extent animals experience emotion beyond core affect, it is likely constrained by such predictive concepts. For instance, while there is some evidence that dogs may have a “concept” of jealousy (and behavioral reactions to it) similar to that in humans (Abdai, Terencio, Fraga, & Miklósi, 2018; Harris & Prouvost, 2014; Cook, Prichard, Spivak, & Berns, 2018, cf Prato‐Previde et al, 2018,b), dogs do not appear to have a “concept” for guilt or the situations that would elicit guilt in humans (Horowitz, 2009). And, conversely, animals may experience discrete emotions for which humans lack concepts, such as the emotion of “sensing the vibrations of a dying family member's voice hundreds of miles away (as might be the case for cetaceans and elephants), or an emotion that results from the physiological consequences of a 250m deep dive that has turned up a favorite food (as may be the case for California sea lions)” (Bliss‐Moreau, 2017, p. 187).…”
Section: Boring Thoughts Other Mindsmentioning
confidence: 99%
“…Thus, to the extent animals experience emotion beyond core affect, it is likely constrained by such predictive concepts. For instance, while there is some evidence that dogs may have a “concept” of jealousy (and behavioral reactions to it) similar to that in humans (Abdai, Terencio, Fraga, & Miklósi, 2018; Harris & Prouvost, 2014; Cook, Prichard, Spivak, & Berns, 2018, cf Prato‐Previde et al, 2018,b), dogs do not appear to have a “concept” for guilt or the situations that would elicit guilt in humans (Horowitz, 2009). And, conversely, animals may experience discrete emotions for which humans lack concepts, such as the emotion of “sensing the vibrations of a dying family member's voice hundreds of miles away (as might be the case for cetaceans and elephants), or an emotion that results from the physiological consequences of a 250m deep dive that has turned up a favorite food (as may be the case for California sea lions)” (Bliss‐Moreau, 2017, p. 187).…”
Section: Boring Thoughts Other Mindsmentioning
confidence: 99%
“…(1) To acclimate the dog to the laboratory, the owner and the dog entered the room together and searched the room for 2 minutes. In many canine laboratory experiments, the acclimation time to the laboratory ranges from 30 seconds to a few minutes, so in our study, we chose 2 minutes [3,10]. The experimenter waited outside the door of the laboratory and, after 2 minutes, the owner and the test dog were escorted into the waiting room.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluating the dog-subjects' dominant rank. Using the questionnaire [3,28] used by Abdai et al in their behavioral experiment of dogs in the triad relationship among owner, dog, and third party (artifacts such as a remote-controlled car or other dogs), we also investigated whether the test dogs were likely to be higher or lower in the domestic pecking order. The questionnaire items are as follow:…”
Section: Checking Dog's Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Dogs are good candidates for jealousy, thanks to their advanced socio-cognitive abilities and long-lasting attachment relationships to humans (Hare & Woods, 2013). Yet results are mixed: whereas some studies have demonstrated dogs' jealous reactions to their owners interacting with a "rival" dog (Abdai, Baño Terencio, Pérez Fraga, & Miklósi, 2018;Cook, Prichard, Spivak, & Berns, 2018;Harris & Prouvost, 2014), other researchers have failed to find evidence for jealousy (Prato-Previde, Nicotra, Fusar Poli, Pelosi, & Valsecchi, 2018a;Prato-Previde, Nicotra, Pelosi, & Valsecchi, 2018b). Such discrepancies may stem from the artificial nature of the experimental paradigms employed: some studies show that dogs exhibit jealous behavioral and neurological responses to fake dogs (Cook et al, 2018;Harris & Prouvost, 2014), but findings that fake dogs are not perceived as real social threats cast doubt on this interpretation (Prato-Previde, Nicotra, Pelosi, et al, 2018, 2018a, 2018b.…”
mentioning
confidence: 99%